Endoscopic findings of the gastric mucosa during long-term use of proton pump inhibitor – a multicenter study. (3rd August 2017) - Kiso, Mariko; Ito, Masanori; Boda, Tomoyuki; Kotachi, Takahiro; Masuda, Kazuhiko; Hata, Kosaku; Sasaki, Atsunori; Kawamura, Toru; Yoshihara, Masaharu; Tanaka, Shinji; Chayama, Kazuaki
Abstract: Background and aim: It is clinically important to diagnose drug-induced gastric lesions correctly. Recently, the use of proton pump inhibitors (PPI) has increased worldwide. The histological features induced by PPI have been reported; however, few reports have described endoscopic findings induced by PPI. Therefore, we aimed to clarify the characteristic endoscopic features in PPI users and associated pathogenic factors. Methods: We prospectively registered 1007 consecutive participants (70 PPI users and 937 nonusers) who underwent endoscopic examination for cancer screening in three hospitals/clinics. Clinical data and endoscopic findings were recorded in the registration forms. We compared the endoscopic features between the two groups and evaluated contributing factors via univariate and multivariate analyses. Results: Multiple white elevated lesions (MWEL) and cobblestone-like mucosa (CLM) were more commonly observed in PPI users compared with nonusers ( p  < .01). Foveolar hyperplastic polyps were also frequently observed in PPI users but were not statistically significantly different ( p  = .06). MWEL and CLM were more frequently observed in older patients than in younger patients. MWEL was more frequently observed in female patients than in male patients; however, CLM was predominantly observed in male patients. Conclusion: MWEL and CLM are characteristic endoscopic features in PPI users. A gender-associated difference was noted in terms of the frequency of these lesions.